SOLUTIONS TO CURRENT PROBLEMS ARISING FROM ICEV USE ENVIRONMENTS - Ferreira, M. A. M. (Quantitative Methods in Economics (Multiple Criteria Decision Making XX), 2020)
With a template consequential from M|G|∞ queue system, we create a model where ICEV-Internal Combustion Engine Vehicles, commonly cars but not only, get idle, in a rare conventional energy ambience, and are either recycled, turning either EV-Electric Vehicles or HEV-Hybrid Electric Vehicles or FCEV- Fuel Cell Electric Vehicles , or dismantled becoming DV-Dismantled Vehicles. The model permits concluding that when the rhythm ICEV become EV, HEV, FCEV, DV is greater than the rate at which they become idle the system has a tendency to balance. Moreover, it is performed a cost-benefit analysis.